Spontaneous and Traumatic Splenic Rupture: Retrospective Clinical, B-Mode and CEUS Analysis in 62 Patients - Rosling, M.; Trenker, C.; Neesse, A.; Görg, C. (Ultrasound International Open, 2018)
Introduction Both B-mode ultrasound and contrast-enhanced ultrasound (CEUS) are well established procedures when diagnosing traumatic splenic ruptures (TSR). To date, there are no data about CEUS patterns in spontaneous splenic ruptures (SSR). It remains unknown whether TSR and SSR differ with respect to clinical characteristics, B-mode and CEUS characteristics.Patients and Methods Between 12/2003 and 2/2010, n=33 SSRs and n=29 TSRs were diagnosed in a tertiary referral center. All patients were examined with B-mode and CEUS, and clinical data and the outcome were retrospectively analyzed.Results Patients with SSR were significantly older than patients with TSR (62 years vs. 44 years; p=0.01). The 4-week mortality was significantly higher in SSR than in TSR (36% vs. 0%; p=0.001). No differences between the grading of TSR and SSR could be shown in B-mode or in CEUS. Notably, CEUS was significantly superior to B-mode with respect to the grading of splenic ruptures (p=0.01). Therefore, therapeutic management was influenced by CEUS.Conclusion There are differences between SSR and TSR, especially concerning clinical data (age, course of disease and mortality). Regarding the sonographic pattern, SSR and TSR show identical grading. When splenic rupture is suspected, CEUS should always be performed to identify patients at risk who require interventional procedures.
Keywords: CEUS; splenic rupture; spleen; rupture